KESEIMBANGAN CAIR-CAIR PADA EKSTRAKSI ASAM-ASAM KARBOKSILAT DARI AIR DENGAN BERBAGAI PELARUT ORGANIK YANG MENGANDUNG TIOA (Liquid - Liquid Equilibrium in Extraction of Carboxylic Acids from Water by Organic Solvents Cont - Perpustakaan UGM, i-lib ([Yogyakarta] : SekolahPascasarjana Universitas GadjahMada, 2000)
ABSTRACT Some models that can be used to predict equilibrium distribution ratio in reactive extraction systems of citric acid-water-(triisooktil amin (TIOA) + organic solvent) had been proposed by previous investigator. In this research, the recommended models considering physical and chemical interactions among molecules in the system will be tested for several other different systems in order to have a general model. Experiments were per-formed for the extraction of acetic, succinic, and citric acids in water using various organic solvents, e.g. methyl isobutyl ketone, dusobutyl ketone, and chloroform containing TIOA. Equal volumes of organic solvent with certain TIOA concentrations and aqueous solutions with certain concentrations of carboxylic acids were added into erlenmeyer flasks and equilibrated in shaker-bath for 4 hours. The two phase were separated after they had been allowed to ,settle for 24 hours. After phase separation, the aqueous phase acid concentrations were determined by colorimetric titration with aqueous NaOH solution, while the organic phase acid concentrations were determined by the same method using alcoholic KOH solution. The experimental data for all systems studied show that the ideal quasi physical approximation model gives the best representation of the equilibrium acid distribution, with the least average relative error (10%) among the other models. The first generalization confirms that stoichiometries are apparent and the final generalized model that included all systems investigated, is of the form: ln[ m CA,, (M) --,- 0.7669 - 0.8347 In CIâT A int " C(W) 1 ) K. f. 1[CA(W)1 with an average relative error of 17.70% or in other different form with an average relative error of 18.42%. (M) Keywords : reactive extraction, carboxylic acid, liquid-liquid equilibrium